2016
DOI: 10.1080/21556660.2016.1252380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telmisartan on kidney function in patients with chronic kidney disease: an observational study

Abstract: Background: Globally the burden of chronic kidney disease (CKD) is rising, an important cause of death and loss of disability-adjusted life years. Activation of the renin-angiotensin-aldosterone system is involved in its pathogenesis. The aim of the present study was to examine the effects of telmisartan (40 mg/day), an angiotensin receptor blocker (ARB) in Indian patients with CKD in real-life setting. Method: This was a prospective observational study. Fifty-six patients (>18 years) diagnosed with CKD were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…On the use of telmisartan 40 mg once daily for 12 months and the reduction was significantly greater than in the amlodipine group (p<0.05). 22 So, in this study showed that telmisartan is effective in the progression of kidney function (BUN and Serum Creatinine) in CKD patients. Based on the results of the study, the impact of public health, especially in health services, is to provide information to medical personnel about the effectiveness of using antihypertensive drugs so that they can improve the quality of services to the community and prevent disease progression.…”
Section: Analysis Of the Use Of Antihypertensives Angiotensin Recepto...mentioning
confidence: 60%
See 1 more Smart Citation
“…On the use of telmisartan 40 mg once daily for 12 months and the reduction was significantly greater than in the amlodipine group (p<0.05). 22 So, in this study showed that telmisartan is effective in the progression of kidney function (BUN and Serum Creatinine) in CKD patients. Based on the results of the study, the impact of public health, especially in health services, is to provide information to medical personnel about the effectiveness of using antihypertensive drugs so that they can improve the quality of services to the community and prevent disease progression.…”
Section: Analysis Of the Use Of Antihypertensives Angiotensin Recepto...mentioning
confidence: 60%
“…The maximum blood pressure-lowering effect occurs about 4 to 8 weeks after starting therapy. 22 Telmisartan is rapidly absorbed from the gastrointestinal tract. Oral bioavailability is dosedependent, about 42% after a 40 mg dose and 58% after 160 mg.…”
Section: Analysis Of the Use Of Antihypertensives Angiotensin Recepto...mentioning
confidence: 99%
“…Известно, что активация РААС, особенно АТ-II, участвует в патогенезе как артериальной гипертензии, так и ХБП [18]. При ХБП БРА являются предпочтительными, поскольку они обладают антипротеинурическим действием вне зависимости от достигнутого уровня АД, за счет селективной блокады АТ рецептора 1 типа [18].…”
Section: Discussionunclassified
“…фармакотерапии результаты свидетельствуют о более выраженном противовоспалительном эффекте телмисартана по сравнению с азилсартаном у больных ГБ на фоне ХБП с ИИ. В литературе существуют противоречивые данные в отношении уровня креатинина при применении телмисартана, некоторые авторы сообщали об отсутствии изменений в процессе лечения, в то же время другие выявили снижение этого показателя [18,34,35]. В исследовании Agrawal А, et al (2016) 55 пациентов с ХБП получали телмисартан в дозе 40 мг/сут.…”
Section: Discussionunclassified
See 1 more Smart Citation